A Case of Motor Neuron Disease Presenting as Dyspnea in the Emergency Department - Park, Hyun Soo (The Korean Academy of Family Medicine, 2012)
Motor neuron disease encompasses a group of progressive neurologic disorders that destroy cells responsible for the control of essential muscles. The disorders are characterized by progressive weakness, muscle atrophy and fasciculation, spasticity, dysarthria, dysphagia, and respiratory compromise. A 66-year-old male presented to the emergency department with progressive dyspnea and, ultimately, respiratory failure. In spite of extensive cardiopulmonary evaluation, a cause could not be identified except aging. After complete history taking, physical and neurologic examination, motor neuron disease was suspected at last. Thus, elderly patients with dyspnea in the emergency department could have hidden diseases beyond the normal aging process.